Current and Future Perspectives of Ethnomathematics as a Program - Rosa, Milton; D$1 (BAmbrosio, Ubiratans; Orey, Daniel Clark; Shirley, Lawrence; Alangui, Wilfredo V.; Palhares, Pedro; Gavarrete, Maria Elena (Cham Springer Nature, 2016)
Mathematics Education; Learning; Teaching
English
Keywords: Education; Mathematics & science; Mathematics Education; Learning; Teaching